PENGARUH APLIKASI PUPUK ANORGANIK DAN HAYATI TERHADAP SIFAT KIMIA TANAH DAN PRODUKSI TANAMAN PADI (Oryza sativa L.) - Lenny Sri Nopriani; R Ay Alvisa Talitha Radiananda; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2023)
The main commodity of food crops cultivated in Indonesia is rice, but rice productivity in Indonesia has decreased. Factors that cause a decrease in rice productivity are land conversion that continues to increase and unbalanced fertilization. Efforts to increase rice yields are by applying a combination of inorganic fertilizers and biological fertilizers. Otherwise, this study focused on studying the effect of the application of a combination of inorganic fertilizers and biological fertilizers on several soil chemical characteristics and rice production in the experimental field of the Faculty of Agriculture, Jatimulyo District, Malang City. Application of biological and inorganic fertilizers with analysys of variance (ANOVA) showed a significant effect on chemical characteristics parameters such as pH and available P. Otherwise, this research showed a significant effect on production, such as the weight of biomass and milled dry grain harvested. Based on this research, the best combination fertilizer is T3 (75% basal inorganic fertilizer + 100% biological fertilizer).